Comprehensive Outlook on Macroeconomic Determinants for Renewable Energy in Malaysia - Mohamed Yusoff N.Y.; Ridzuan A.R.; Soseco T.; Wahjoedi; Narmaditya B.S.; Ann L.C. (MDPI, 2024)
Mitigating global warming has been a challenge, and policymakers are responding to this issue by strengthening the commitment to enhance the renewable energy target from 20 to 31 percent in 2025 for Malaysia. However, adopting renewable energy in stages based solely on microeconomic factors, such as the price of energy, is insufficient. Thus, it is essential to investigate the macroeconomic variables that influence the share of renewable energy in Malaysia. In detail, this study introduces selected macroeconomic indicators, including gross domestic investment, domestic investment, foreign direct investment, trade openness, urbanization, financial development, and carbon emissions level, and their impact on renewable energy in Malaysia. The study utilized ARDL (Auto-Regressive-Distributed Lag) estimation based on annual time series data spanning 50 years of observations, beginning in 1971 and ending in 2020. Long-run elasticities show that greater economic development and urbanization increase the proportion of renewable energy. In contrast, increased foreign investment, trade liberalization, and carbon emissions could reduce the use of these clean energies. This paper concludes with a policy recommendation that could assist the country in achieving its goal of implementing a low-carbon, renewable energy-focused state policy. 2023 by the authors.